Early mortality in elderly patients undergoing treatment for multiple myeloma in real-world practice. Issue 6 (June 2018) - Xia, Jun; Wang, Lingling; Zhou, Xin; Wang, Jing; Wang, Huan; Guo, Hongfeng
Objectives: This study was performed to analyze the risk factors for early mortality (EM) in elderly patients undergoing treatment for multiple myeloma (MM) in real-world clinical practice. Methods: Retrospective data from 108 elderly patients who were newly diagnosed with MM from January 2007 to July 2015 were analyzed in a single hematology center. EM was defined as death of any cause within 12 months after diagnosis. A multivariate regression model was used to evaluate EM. Results: EM occurred in 16 (14.8%) elderly patients with newly diagnosed MM. The most common cause of death was infection (10/16, 62.5%). In the multivariate analysis, only an age of ≥75 years, International Staging System (ISS) stage III disease, and high lactate dehydrogenase concentration were significantly and independently associated with EM. Conclusion: Our results suggest that infection is the leading cause of EM in elderly patients with MM. An age of ≥75 years, ISS stage III disease, and a high lactate dehydrogenase concentration are significant predictors of EM. We should further target this higher-risk patient population to define personalized therapy with which to improve outcomes.